Level of Focus of Organizations Operating in Slovakia on Flexible Organizational Structure - Stachova, Katarina; Stacho, Zdenko (International Review of Management and Marketing, 2017)
Flexible organisational structure is characterised by the creation of temporary units (teams) within a basic departmental structure to solve a particular difficult task, important for the organisation and limited by time. It can be stated on its grounds that team work is the basis of innovative organisation operation. However, fact that organisations most often use individuals and not the creation of a team specialised in the given issue in solving of new, important and demanding projects and tasks sounds negative. If organisations want to create so called innovative environment, it is necessary to focus on organisational structure, while it is necessary to realise that different organisational structures are appropriate for different types of organisations. Presumption which was the basis of our analysis of organisational structure flexibility was the fact that organisational flexibility results from its ability to respond to changing conditions and new situations. Therefore, we monitored the frequency of characteristics like adaptation of organisational structure to changing conditions and delegation of operational decisions to line managers. However, the research implied that only a smaller part of organisational structures of the analysed organisations fulfills these characteristics. Keywords: Flexible organisational structure, innovative environment, analyse, organisations JEL Classifications: E24, J24, C44, O15, M12